Effectiveness of short sprint interval training in women with major depressive disorder: a proof-of-concept study - Ribeiro, Jéssica Alves; Schuch, Felipe Barreto; Tonello, Laís; Meneghel Vargas, Kleber F.; Oliveira-Junior, Silvio A.; Müller, Paulo T.; Boullosa, Daniel (Frontiers in Psychiatry, 2024)
High-intensity intermitent training has emerged as an opon for treang major depressive disorder (MDD). However, short sprint training (sSIT), an efficient HIIT modality, has not been tested yet for this purpose. The sSIT has been proven to induce the same metabolic adaptaons, with the advantage of promong lower muscle fague than other HIIT protocols. Seventeen adult women diagnosed with moderate/severe MDD were randomly allocated into a sSIT group (n=9) or a control condion (n=8). The sSIT group completed, over two weeks, six 6-10-min sessions which consisted of 3-12 "all out" sprints of 5 s interspersed with low-intensity recovery of 30-45 s. The week before and aer the intervenon, both groups were evaluated with the Hamilton Depression Rang Scale of 21-itens (HAM-D21), and for physical fitness and incidental physical acvity. The sSIT group exhibited significant improvements for HAM-D21 scores (24.6±8.2 vs. 16.8±10.1), maximum aerobic power (140±15 vs. 155±15 W), countermovement jump (13.0±3.4 vs. 14.9±3.1 cm), % of body fatness (32.4±4.4 vs. 29.3±3.8%), and 4-days number of steps (13,626±11,309 vs. 16,643±15,371) aer the training period when compared to the control group. Less than 1 hour of a sSIT protocol over two weeks have demonstrated to reduce depressive symptoms, while improving aerobic fitness and body composion, and increasing incidental physical acvity in a sample of women diagnosed with MDD.